O traje como indutor para o jogo teatral: uma experiência prática no Ensino Básico - RAMOS, Maciel Mourão (2023)
The present study is a methodological proposal of teaching in theater and aims to experience and reflect on the potential of the scenic costume as an inducer for theatrical practice in formal education. The research sought the results from the Art classes, carried out with elementary school II students in the city of Caxias Maranhão. For the development of this research, it was necessary to divide it into four pedagogical moments: the first moment corresponded to the realization of interaction games, the second moment the creation of a collection together with the participating students, the third moment corresponded to the organization and preparation of the costume trunk with the collected clothes, the fourth moment the interaction of the students with the costumes and scene play with the characters created from the costumes and in the fifth moment there was a debate on experiences. The process made it possible to culminate in this study and analysis of the experiences reported by the students, what makes up the present pedagogical proposal.